Pengembangan Kampung Wisata Berbasis Kearifan Lokal Di Dusun Kamal Desa Karangsari Kecamatan Pengasih Kabupaten Kulun Progo - Hayati, Jurni; Surgawati, Iis; Rahayuningrat, Rahayuningrat (Universitas Bengkulu, 2023)
This study aims to identify the physical and non-physical potential of Kamal Hamlet, Karangsari Village, examine the extent of community participation in the development of Kamal Tourism Hamlet Karangsari Village, then researchers will design a tourism village model based on local wisdom that can accelerate the development of Kamal Tourism Hamlet Karangsari Village so that the people can enjoy the results of their existence the Tourism Village. The type of research used in this research is descriptive qualitative. Sources of research data obtained from interviews, observation, and documentation in 2019. The data analysis technique used in this study is an interactive model. Based on the research results, the physical potential in Kamal Tourism Hamlet Karangsari Village is natural and cultural potential. While the non-physical potential is the Karangsari community involved in the development of a tourist village, the level of community education, land tenure of yards, fields, gardens and rice fields, as well as the main household income per month. The tourism development model that can be used in Kamal Tourism Hamlet Karangsari Tourism Village is a development model based on local wisdom, namely nature and culture based because Kamal Tourism Hamlet Karangsari Village has various natural and cultural potentials. Keywords : Physical Potential1, Non-Physical Potential2, Community Participation3, Local Wisdom 4